Alachlor and Metribuzin Herbicide on N2-fixing Bacteria in a Sandy Loam soil - Das, Shaon Kumar; Mukherjee, Irani; Roy, Aniruddha (International Journal of Bio-resource and Stress Management, 2023)
Herbicides interact with soil organisms and their metabolic activities and may alter the physiological and biochemical behavior of soil microbes. Some microbial groups are capable of using applied pesticide as a source of energy and nutrients to multiply, whereas the pesticide may be toxic to other organisms. Laboratory experiment was conducted to investigate the effect of two selective systemic herbicides viz., alachlor and metribuzin, at their recommended field rates (2.0 and 0.4 kg a.i. ha-1, respectively) on the growth and activities of non symbiotic N2-fixing bacteria in relation to mineralization and availability of nitrogen in a sandy loamsoil of India. Both the herbicides, either singly or in a combination, stimulated the growth and activities of N2-fixing bacteria resulting in higher mineralization and availability of nitrogen in soil. The single application of alachlor increased the proliferation of aerobic non-symbiotic N2- fixing bacteria to the highest extent while that of metribuzin exerted maximum stimulation to their N2-fixing capacity in soil. Both the herbicides, either alone or in a combination, did not have any significant difference in the stimulation of total nitrogen content and availability of exchangeable NH4+ in soil while the solubility of NO3− was highly manifested when the herbicides were applied separately in soil. The effect of combined application of the herbicides was more or less at par with their single application.